Adiaphorisation and the digital nursing gaze: liquid surveillance in long-term care - Rubeis, Giovanni (Nursing philosophy, 2022)
The nursing gaze, that is the specific ways of observing the patient in nursing practice, has been the object of ethical debates for decades. It has been argued that the specific feature of observing patients in nursing is the stereoscopic vision that allows nurses to see the patient at the same time as a subject and a body. However, with the increased use of technology in nursing and the focus on quantifiable biomedical data, some commentators see a shift from the view of the patient as subject to the patient as body, which results in a de-humanisation and objectification of patients. The new digital technologies in patient monitoring and surveillance add a further dimension to this topic. It is yet unclear how digital technologies affect the nursing gaze, and with it, nursing practice. Furthermore, the ethical implications of the digitally enhanced nursing gaze have yet to be analysed. It is the purpose of this study to make a first step in this direction. By focusing on digitally enhanced monitoring technologies in long-term care, these technologies are interpreted as liquid surveillance, an approach introduced by Zygmunt Bauman. The Baumanian concept of adiaphorisation, that is the detachment of social action from moral evaluation, is used as normative framework of the analysis. The analysis shows that the tendency to remove surveillance practices from moral evaluation by framing them as enablers of an active, healthy life and as tools for caring for the vulnerable, the stereoscopic vision of the nursing gaze is undermined.